Merapi Disaster Impact on The Dairy Business in The District of Sleman - Nyak Ilham; Atien Priyanti (Indonesian Center for Animal Research and Development, 2011)
Merapi disaster with a variety of volcanic material caused fatalities or death and directly influenced on the health of cattle. Both of these effects in addition to psychological effects that cause farmers panic and economically are very harmful. This study aims to analyze the impact of Merapi disaster on dairy cow production and estimate the economic losses on the dairy cattle business. The analysis showed that Merapi disaster caused the death of livestock and reduced milk production. Livestock deaths are mainly caused by hot clouds, lava and ash that consumed through food and the respiratory tract. Decrease in milk production varies from 6.7 percent to 84 percent. Cows that are left displaced and not given food and drink for four days obviously decreased in milk production. The death of livestock, disruption of institutional marketing input and output, falling livestock prices and the decline in milk production resulted in losses IDR. 21.0 billion. Key words: Impact, Merapi eruption, dairy cow